Hydrogeochemical features of surface water and groundwater contaminated with acid mine drainage (AMD) in coal mining areas: a case study in southern Brazil - Galhardi, Juliana Aparecida [UNESP] (2016)
Effects of acid mine drainage (AMD) were investigated in surface waters (Laranjinha River and Ribeirao das Pedras stream) and groundwaters from a coal mining area sampled in two different seasons at Figueira city, Parana State, Brazil. The spatial data distribution indicated that the acid effluents favor the chemical elements leaching and transport from the tailings pile into the superficial water bodies or aquifers, modifying their quality. The acid groundwaters in both sampling periods (dry: pH 2.94-6.04; rainy: pH 3.25-6.63) were probably due to the AMD generation and infiltration, after the oxidation of sulfide minerals. Such acid effluents cause an increase of the solubilization rate of metals, mainly iron and aluminum, contributing to both groundwater and surface water contamination. Sulfate in high levels is a result of waters' pollution due to AMD. In some cases, high sulfate and low iron contents, associated with less acidic pH values, could indicate that AMD, previously generated, is nowadays being neutralized. The chemistry of the waters affected by AMD is controlled by the pH, sulfide minerals' oxidation, oxygen, iron content, and microbial activity. It is also influenced by seasonal variations that allow the occurrence of dissolution processes and the concentration of some chemical elements. Under the perspective of the waters' quality evaluation, the parameters such as conductivity, dissolved sodium, and sulfate concentrations acted as AMD indicators of groundwaters and surface waters affected by acid effluents.